Sedimentology and Mineralogy of Sedimentary Sequences in Nanim Field in the Niger Delta basin, Nigeria. - Chiazor, Fortune I.; Ideozu, Richmond U. (European Journal of Applied Sciences, 2023)
A total of nineteen ditch cuttings from the sedimentary sequence of Nanim Field, were subjected to both sedimentological and mineralogical analysis with the aim of investigating the mineralogical composition of the studied section (1810 m - 2650m) in the study area. The shale samples were grinded, pulverized and sieved with less than 75μm and analyzed using X-ray diffraction techniques (XRD) for mineralogical composition. Results of the sedimentological analysis, suggests four lithofacies made up of sandstone, shaly sand, shale and sandy shale in he studied section. The studied section has been interpreted as a shallow marine environment divided into two broad lithofacies sequences made up of beach sand (1810 m - 2290 m.) and upper shoreface (2300 m – 2650m) respectively. The beach sand sequences comprises thick sands, brownish, grey to black, fine to coarse grained, whereas the upper shoreface sequence is essentially a heterogeneous sequence of alternating sand medium to very fine grained sand and shale - grey. Results from the XRD analysis shows that the mineralogical composition of the basal part (upper shoreface) of the studied section is characterized by kaolinite a dominant in sediments of fluviatile environments and is known to concentrate in many near-shore sediments (shallow marine) with a decrease in abundance from the shoreline as other clay minerals increase basinward.